The role of clopidogrel resistance-related genetic and epigenetic factors in major adverse cardiovascular events among patients with acute coronary syndrome after percutaneous coronary intervention - Giantini, Astuti; Timan, Ina S.; Dharma, Rahajuningsih; Sukmawan, Renan; Setiabudy, Rianto; Alwi, Idrus; Harahap, Alida R.; Listiyaningsih, Erlin; Partakusuma, Lia G.; Tansir, Arif R.; Sahar, Windy; Hidayat, Rakhmad (Frontiers in Cardiovascular Medicine, 2023)
Despite undergoing percutaneous coronary intervention and receiving clopidogrel therapy, some acute coronary syndrome patients still experience major adverse cardiovascular events. Clopidogrel resistance, which may be regulated by genetic and epigenetic factors, possibly plays a role in MACE. This study aimed to determine the relationship between genetic factors (CYP2C19 and P2Y12 polymorphisms) and epigenetic factors (DNA methylation of CYP2C19 and P2Y12 and miRNA-26a expression) and their effects on MACE in post-PCI patients. Post-PCI patients who received a standard dosage of clopidogrel at Harapan Kita Hospital from September 2018 to June 2020 were included. MACE was observed within one year after PCI. Platelet aggregation was examined using light transmission aggregometry (LTA). DNA methylation of CYP2C19 and P2Y12 was examined using the bisulfite conversion method. CYP2C19 and P2Y12 polymorphisms and miRNA-26a expression were examined using quantitative real-time polymerase chain reaction (qRT-PCR). Among 201 subjects, 49.8% were clopidogrel resistant, and 14.9% experienced MACE within one year after PCI (death was 7.5%). Hypomethylation of CYP2C19 (P = 0.037) and upregulated miRNA-26a expression (P = 0.020) were associated with clopidogrel resistance. CYP2C19*2/*3 polymorphisms (P = 0.047) were associated with MACE in one year. This study showed that hypomethylation of CYP2C19 and upregulated miRNA-26a expressions increase the risk of clopidogrel resistance in post-PCI patients, but we did not find any correlation between clopidogrel resistance and MACE. However, CYP2C19*2/*3 polymorphisms were the predictor factors of MACE in one year.